Pengaruh Komposisi Media Tanam Arang Sekam Padi Terhadap Pertumbuhan dan Produksi Jagung Pulut ( Zea mays ceratina L. ) - Tia Novianti; Novilda Elizabeth Mustamu; Hilwa Walida; Fitra Syawal Harahap (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
Glutinous corn has a weakness in its production which is still low, especially in the Labuhanbatu area. This study aims to determine the growth and yield of maize pulut (Zea mays certaina L) from the administration of various doses of rice husk charcoal. This research was conducted in an experimental area in Ujung Batu Hamlet, Perbaungan Village, Bilah Hulu District, Labuhanbatu Regency, North Sumatra. This research was conducted from April to June 2021. The research design used was a non-factorial Randomized Block Design (RAK) with 4 treatments, namely M0: Ultisol soil without rice husk charcoal 10 kg, M1: (4 kg soil: 6 kg rice husk charcoal ), M2 : (5 kg soil : 5 kg rice husk charcoal) and M3 : (6 kg soil : 4 kg rice husk charcoal). Parameters observed were plant height, number of leaves, flowering age and cob weight. The data were analyzed using the F test with a confidence level of 5%. The results showed that the best treatment was to use the M2 treatment (5 kg soil: 5 kg rice husk charcoal). Keywords: corn, growth, rice husk charcoal